Polysaccharide 3D Printing for Drug Delivery Applications - Alexandra Zamboulis; Georgia Michailidou; Ioanna Koumentakou; Dimitrios N. Bikiaris (MDPI AG, 2022)
3D printing, or additive manufacturing, has gained considerable interest due to its versatility regarding design as well as in the large choice of materials. It is a powerful tool in the field of personalized pharmaceutical treatment, particularly crucial for pediatric and geriatric patients. Polysaccharides are abundant and inexpensive natural polymers, that are already widely used in the food industry and as excipients in pharmaceutical and cosmetic formulations. Due to their intrinsic properties, such as biocompatibility, biodegradability, non-immunogenicity, etc., polysaccharides are largely investigated as matrices for drug delivery. Although an increasing number of interesting reviews on additive manufacturing and drug delivery are being published, there is a gap concerning the printing of polysaccharides. In this article, we will review recent advances in the 3D printing of polysaccharides focused on drug delivery applications. Among the large family of polysaccharides, the present review will particularly focus on cellulose and cellulose derivatives, chitosan and sodium alginate, printed by fused deposition modeling and extrusion-based printing.